Giuliani in Izmir: restructuring of the Izmir public order police and criminalization of the urban poor - Gönen, Zeynep (Critical criminology, 2013)
This paper examines the recent restructuring of the Izmir Public Order Police, launched in 2006 to address the rise in urban crime in Izmir, Turkey. Transforming itself into a professionalized and effective organization against ‘criminals’ and claiming to institute a proactive policing strategy, the Izmir police have expanded their control over the urban space, while specifically targeting the poor segments and populations in the city, and carefully distinguishing them from the ‘respectable’ and ‘innocent’ citizens. The paper details the elements of the new policing in Izmir and demonstrates that it has rested on profiling and criminalization of the ethno-racially differentiated urban poor populations, especially Kurdish migrants. The new policing in Izmir, the paper argues, is not an isolated case but an example of the neoliberal transformations around the globe, where regulation and management of urban poor populations are increasingly relegated to the penal rather than the social state.